Environmental Impact Assessment : A Guide to Best Professional Practices - Eccleston, Charles H. (Boca Raton: CRC Press, 2023)
The author introduces best professional practices (BPP) for preparing such EIAs that is intended to meet decision-making and regulatory expectations. He supplies a comprehensive and balanced skill set of tools, techniques, concepts, principles, and practices for preparing these assessments. He also includes directions for developing a comprehensive Environmental Management Systems which can be used to monitor and implement final decisions for such analyses. While the book references the U.S. National Environmental Policy Act (NEPA), most of this guidance is generally applicable to any international EIA process consistent with NEPA. With thorough coverage of all aspects of assessments, the book presents a theoretical introduction to the subject as well as practical guidance. It delivers state-of-the-art tools, techniques, and approaches for resolving EIA problems.
Includes index and acronym list
Keywords: Environmental impact analysis; Environmental policy; Environmental law; Sustainable development$1 (BEnvironmental aspectss; Environmental management